2010
DOI: 10.1007/s11904-010-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

HIV, Antiretroviral Therapies, and the Brain

Abstract: While combination antiretroviral therapy (CART) has decreased the incidence of HIV-associated dementia, the severest form of HIV-associated neurocognitive disorders (HAND), mild neurocognitive disorder and asymptomatic neurocognitive impairment continue to persist, and there is evidence that neurocognitive deficits present even in acute HIV infection. Recent studies demonstrate that CART regimens with higher central nervous system (CNS) penetration effectiveness ranks may improve neurocognitive functioning. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 49 publications
0
46
0
Order By: Relevance
“…The continued presence of HAND despite cART could result from non-mutually-exclusive factors including irreversible injury prior to initiating cART, persistent HIV-1 RNA in the brain [7], antiretroviral treatment toxicities [810], and/or persistent low level inflammation [11]. Currently, the diagnosis of HAND requires neuropsychological performance (NP) testing and self-reported assessment of activities of daily living with the following classifications used: neuropsychologically normal, asymptomatic neurocognitive impairment (ANI), mild neurocognitive disorder (MND), or HIV associated dementia (HAD) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The continued presence of HAND despite cART could result from non-mutually-exclusive factors including irreversible injury prior to initiating cART, persistent HIV-1 RNA in the brain [7], antiretroviral treatment toxicities [810], and/or persistent low level inflammation [11]. Currently, the diagnosis of HAND requires neuropsychological performance (NP) testing and self-reported assessment of activities of daily living with the following classifications used: neuropsychologically normal, asymptomatic neurocognitive impairment (ANI), mild neurocognitive disorder (MND), or HIV associated dementia (HAD) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Peptide therapeutics are generally not transported from the blood to the brain, failing to cross the brain capillary endothelial wall that makes up the blood-brain barrier (BBB) in vivo (40), and this lack of brain distribution has precluded potential benefits, for example, in the treatment of HIV-1 dementia and viral encephalitis (41). For HIV-1, the peptide fusion inhibitor enfuvirtide is used as a salvage therapy for multidrug-resistant HIV-1-infected patients; however, its clinical use is limited by a short half-life, poor biodistribution properties, and the parenteral route of delivery (39).…”
mentioning
confidence: 99%
“…Prospective studies are needed to determine if early diagnosis and initiation of antiretroviral therapy would reduce the burden of NCI among HIV-infected persons. 26 A recent study showed that patients with early HIV infection had similar neurocognitive functioning compared to HIV-uninfected persons, suggesting that detrimental effects of HIV on the brain may not occur immediately, potentially providing an opportunity for early intervention. 27 Clinical trials are underway, including a substudy of the Strategic Timing of Antiretroviral Treatment (START) trial, examining neurocognitive functioning among those treated immediately compared to later in their disease course.…”
mentioning
confidence: 99%